Influencers-Activists ’Eco’, Perceptions and Feelings: An Analysis from Neuromarketing - Piqueiras, Paloma; Herrera-Capriz, Mariana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
In the field of social networks, people publicly committed to social, environmental or political causes are considered “activist influencers.” This article takes this emerging figure as a reference with the aim of analyzing his messages on Instagram and the impact generated by them on the audience. Through a survey and neuromarketing techniques (Eye Tracking), it has been possible to: 1) extract results on the implicit responses (attention, visual routes and emotion) produced by the messages of “activist influencers” in the environmental field and; 2) identify the explicit responses (association, coherence and credibility) of the defended causes.